2009
DOI: 10.1088/1478-3975/6/4/046014
|View full text |Cite
|
Sign up to set email alerts
|

Long-range energy transfer in proteins

Abstract: Proteins are large and complex molecular machines. In order to perform their function, most of them need energy, e.g. either in the form of a photon, as in the case of the visual pigment rhodopsin, or through the breaking of a chemical bond, as in the presence of adenosine triphosphate (ATP). Such energy, in turn, has to be transmitted to specific locations, often several tens ofÅ away from where it is initially released. Here we show, within the framework of a coarse-grained nonlinear network model, that ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 68 publications
4
85
0
Order By: Relevance
“…Long range non-additivity is expected in allosteric proteins (50) but also is common in many protein classes (51). In addition, energy in a protein can jump from site to site, covering large distances (52). A complex arrangement of interactions between distant amino acids is prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Long range non-additivity is expected in allosteric proteins (50) but also is common in many protein classes (51). In addition, energy in a protein can jump from site to site, covering large distances (52). A complex arrangement of interactions between distant amino acids is prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…This process is accompanied by large structural rearrangements if there is an energy exchange between protein regions with "discrete breathers" (localized excitations). [28][29][30][31] The conformational selection paradigm implies that "discrete breathers" should be located close to ligand-binding sites. Although at first sight, the conformational selection paradigm and the approach that we used in this study look different, the similarity between them becomes clear if we make an analogy between "discrete breathers" and the eigenmodes of the burial mode model energy function 12 -in both descriptions, ligand-binding suppresses one mode and stimulates another, coupling large scale motions to the transduction of small forces.…”
Section: Discussionmentioning
confidence: 99%
“…Using an anharmonic model, it was shown that "discrete breathers", localized vibrational modes easily form in proteins at the stiffest regions, and are able to pump and store energy from neighboring sites. Thus, energy can 'jump' from site to site via this mechanism, often covering long distances [119,120]. In a Gaussian network model, the correlations between the energy fluctuations of residues were calculated, and were found to define an interaction pathway which was similar to the pathway defined by the co-evolving network of residues in the PDZ domain [121].…”
Section: Energy Propagation In Proteinsmentioning
confidence: 99%